DP-b99 Does Not Improve Recovery following Acute Ischemic Stroke - Vinall, Phil (MD Conference Express, 2013)
Despite encouraging preclinical and Phase 2 trial results [Angel I et al. Drug Dev Res 2002; Striem S et al. Neural Plast 2003; Rosenberg G et al. Stroke 2004; Diener HC et al. Stroke 2008; Barkalifa R et al. Eur J Pharmacol 2009], data showed that DP-b99, a lipophilic moderate-affinity chelator of zinc, did not improve outcome in patients with acute hemispheric ischemic stroke [Lees KR et al. Stroke 2013]. The Efficacy and Safety Study of DP-b99 in Treating Acute Ischemic Stroke trial [MACSI] was a Phase 3 study conducted to determine if intravenous administration of DP-b99 up to 9 hours following stroke onset and then for 3 additional days is effective in improving long-term outcomes.